(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This paper explores the significance of developing algorithmic thinking in computer science students, emphasizing its role in fostering problem-solving abilities, logical reasoning, and computational skills. Algorithmic thinking is fundamental for tackling complex tasks, designing efficient solutions, and advancing in programming and software development. The study examines various pedagogical approaches and strategies that enhance algorithmic thinking, including hands-on coding exercises, project-based learning, and collaborative problem-solving. The integration of algorithmic thinking in the educational process not only improves technical skills but also enhances students’ overall analytical abilities. The findings highlight the importance of structured methodologies in building algorithmic competence, contributing to the formation of well-rounded and adaptable computer science professionals.